Perspectives of nurses and patient representatives on the morally competent nurse: An international focus group study - Keogh, Brian; Mc Cabe, Catherine (My University, 2025)
Background: Across the world, healthcare systems have become increasingly complex, making it more difficult for nurses to act ethically when faced with moral dilemmas. The COVID-19 pandemic in particular revealed ethical challenges, highlighting the need for nurses to attain high levels of moral competence. Nurses who attain moral competency provide superior patient care because they have integrated clinical competence with sensitivity to moral values. Under- standing what comprises moral competence in nursing is crucial to stimulate and support consistent ethical behaviour. However, most studies to date on moral competence in nursing have been conducted at a national level and only from a particular stakeholders’ perspective, thereby limiting their utility. Objective: To explore and document the characteristics of the morally competent nurse from the perspectives of nurses and patient representatives practicing in Europe. Design: A descriptive qualitative study was conducted. Methods: Semi-structured focus group discussions were conducted to collect data. Data were analysed with a descriptive thematic method.
PUBLISHED
Keywords: Qualitative research; Patient representatives; Nursing; Multinational perspectives; Moral competence; Ethics; Focus groups